EVALUASI PROGRAM WAJIB BELAJAR PENDIDIKAN DASAR DI DKI JAKARTA PADA PERIODE 2008-2011 - HENRY ERYANTO; DARMA RIKA (Fakultas Ekonomi Universitas Negeri Jakarta, 2014)
Abstract This study aimed to evaluate the Compulsory Basic Education Programme period 2008-2011 in Jakarta and knew the extent of the success of the program, and formulate policy recommendations to improve this activity in the future . This study uses the CIPP evaluation process to assess whether the program is appropriate to proceed or not. From the research, it is seen that in the context of the stage success indicators compulsory education program, it can be concluded that the implementation of the law that underlies the program has not done well. Referring to the input stage of program success indicators compulsory education, it can be concluded that the population of school age enrolled in school at that level has been well absorbed. Referring to the indicators of the success of the process stages of compulsory education program, it can be concluded that the stage of the process is quite successful. As well as referring to the indicators of the success of the product phase of compulsory education program, it can be concluded that the stage of successful products, because its value at a high level of completeness that range from 94% -103 %. Keywords: Basic Education Programme, CIPP Evaluation, DKI Jakarta.